2019
DOI: 10.1159/000503321
|View full text |Cite
|
Sign up to set email alerts
|

Pain, Anxiety, Depression, and Quality of Life in Patients with Vulvodynia

Abstract: Background/Aims: The term vulvodynia refers to vulvar pain of unknown origin lasting at least 3 months. Psychiatric comorbidities are a common feature and, along with pain, may severely affect patients' wellbeing. We aimed to determine the characteristics of pain in vulvodynia, to correlate characteristics with symptoms of anxiety and depression, and to analyse the impact of these factors on patients' quality of life. Methods: This cross-sectional observational study analysed pain, anxiety, and depression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…The women surveyed scored the highest scores in the psychological and environmental domains of the WHOQoL-BREF questionnaire. Although the women surveyed scored the highest in the psychological domain, some studies show that women with vulvodynia suffer from anxiety and depression [ 56 , 57 ]. In a Spanish study by Tribó et al [ 56 ], 61.7% of vulvodynia patients reported suffering from anxiety and 24.7% were depressed.…”
Section: Discussionmentioning
confidence: 99%
“…The women surveyed scored the highest scores in the psychological and environmental domains of the WHOQoL-BREF questionnaire. Although the women surveyed scored the highest in the psychological domain, some studies show that women with vulvodynia suffer from anxiety and depression [ 56 , 57 ]. In a Spanish study by Tribó et al [ 56 ], 61.7% of vulvodynia patients reported suffering from anxiety and 24.7% were depressed.…”
Section: Discussionmentioning
confidence: 99%
“…The pain does not only affect sexual function and satisfaction [ 66 ], but is also associated with psychological distress [ 67 , 68 ], relational dissatisfaction, and a lower quality of life [ 59 ]. Yet, it is a neglected pain condition [ 69 ], and many women are left without correct diagnosis and treatment [ 70 ]. Other typical symptoms include allodynia within the vulvar vestibule for at least 3 to 6 months and erythema at the inferior introital sulcus, medial to the Hart line, particularly in the periosteal areas of the vestibular glands [ 62 , 63 ].…”
Section: Vulvodynia and Vestibulodyniamentioning
confidence: 99%
“…Women with vulvar vestibulitis syndrome are homozygous for allele 2 of the IL-1RA gene (IL1RN*2), a phenotype linked to ulcerative colitis, Crohn’s disease, and systemic lupus erythematosus, according to one explanation. Proinflammatory reactions are more protracted and intense in persons with this phenotype than in those with other IL-1RA genotypes [ 70 ]. Another notion is that unpleasant environmental stimuli cause neurogenic inflammation of the vulvar vestibule ”end-organ,” resulting in parasympathetic efferent and visceral nociceptive afferent hyperactivity.…”
Section: Vulvodynia and Vestibulodyniamentioning
confidence: 99%
“…The link between pain and anxiety has proven to be increasingly significant, and both act as risk factors for each other. Multiple lines of evidence have shown that clinically, patients suffering from pain also experience anxiety ( Michaelides and Zis, 2019 ; Tribo et al, 2020 ). Proper clinical treatment for comorbid anxiety symptoms in pain (CASP) is a significant challenge since the mechanism is not fully understood.…”
Section: Introductionmentioning
confidence: 99%